Can the Caribbean benefit from the International IPR Regime? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
The 10th Anniversary of the Agreement on Trade-Related Aspects of Intellectual Property Rights ('TRIPS') was recently commemorated in Brussels by a Conference organized by the European Union. In the 10 years, the Caribbean countries have made major strid